Therapeutic procedures in shoulder impingement syndrome (SIS) for professionally active people: randomized research - Agnieszka Skopowska; Maciej Biernacki; Monika Dekowska; Małgorzata Łukowicz; Sielski Łukasz; Agnieszka Filarecka (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2018)
Objectives. Pain and limitation of motions in the glenohumeral joint are frequently the consequence of the shoulder impingement syndrome (SIS). Misdiagnosis or improper treatment of the illness may effect in a serious functional impairment of the upper limb. The treatment, dependent on the medical condition, involves: rest, NSAID therapy, physiotherapy as well  as kinesitherapeutic procedures. The aim of the research was to conduct a detailed diagnosis of the shoulder impingement syndrome and the efficacy assessment of the matched rehabilitating procedures considering the symptoms. Material and methods. The research was conducted in 39 people aged 30 to 81 treated for SIS. 85% of the respondents were professionally active.In order to assess the efficacy of the therapy the following were carried out: the pain assessment test, functional tests (Neer's, Ludington's, Hawkins', Apley's, Job's and the active painful arc test) as well as measurements of the active range of motion of the joint. The patients were subjected to two kinds of physiotherapy - ultrasound therapy (US) procedures and the short wave diathermy (SWD), both connected with procedures aiming at mobilization of the shoulder complex and off-load exercises. The outcome was submitted to statistic analysis. Results. The results obtained in both groups of patients were compared via the Mann-Whitney U test. No significant differences between the SWD and the US groups in the efficacy of the conducted procedures were observed. The data analysis within therapeutic groups revealed the existence of significant differences (p<0,01) before and after the therapy, in the VAS and Laitinen scales as well as in the measurements of the range of motions. Conclusions. The outcome of both conducted therapies in both research groups included: decrease in pain, increase in the range of motions of the glenohumeral joint and improved function of the upper limb. Both procedures may be successfully employed in the treatment of SIS in professionally active people.